The effect of service quality towards customer satisfaction of Islamic bank in Kuantan Pahang / Faresya Zunaida Mohd Zubair - Mohd Zubair, Faresya Zunaida (Faculty of Business and Management, 2015)
The goal of this study is to identify the effects of service quality towards customer satisfaction at Islamic bank in Jalan Tun Ismail Kuantan, Pahang. The study also aims to examine the relationship between service quality (Reliability, Tangibility, and Responsiveness) and customer satisfaction, to investigate the most influencing factor of service quality (Reliability, Tangibility, and Responsiveness) towards customer satisfaction and to know the best service quality (Reliability, Tangibility, and Responsiveness) provided at Islamic Bank in Kuantan area. A sample of 103 banking customers was drawn from Islamic bank in Jalan Tun Ismail. The questionnaire was developed for this study was based on SERVQUAL model that identified the influence three from five dimensions (reliability, tangibility and responsiveness) in banking service environments on customer satisfaction. The results indicate that the three of SERVQUAL dimensions have a positive influence on customer satisfaction. Responsiveness was more significant in contributing to customer satisfaction in Jalan Tun Ismail area while reliability follows after and tangibility was the least significant.